Pemanfaatan Informasi Teknologi Mangga (Kasus Di Kecamatan Sedong Kabupaten Cirebon) - Junika Megawaty Pasaribu; Ninuk Purnaningsih; Retno Sri Hartati Mulyandari (Institut Pertanian Bogor, 2015)
Mango farmer need a technology to improve the production and the quality of mango. This study was aimed to analyse the factors related to the use of information by mango farmer, the relationship of farmer characteristics, level of information need, and level of information access with the use of information sources by the mango farmer, and to analyze the relationship between the use of information sources and the level of utilization of technology information by the mango farmer. A survey was conducted towards 65 farmers as respondents in Sedong Subdistrict, Cirebon Regency.The results showed that in the use of information sources of mango farmer, a few of information sources were used, the intensity of information access was low and the level of information appropriateness were low and very high. The influential factors towards the use of information sources were age, level of formal and non-formal education, scale of business, level of income, level of information need of cultivation, post-harvest, and marketing, and so level of easiness and affordability to access information. The level of utilization of information were very high to enhance the knowledge, very low to be applicated, and high to be forwarded to others. A very significant possitive correlation was found between the use of information sources and utilization of information.Keywords: utilization of information, mango, information need, information sources